Oikeuden resilienssi, perusoikeudet ja kokonaisturvallisuus - Aine, Antti; Nurmi, Veli-Pekka; Valtonen, Vesa (Lakimies, 2025)
Legal resilience, fundamental rights, and comprehensive security The basis on which countries prepare for emergencies and severe disruptions has been changing over the past decades. Societal development has led to security threats becoming more dynamic and interdependent. The changes in the security environment have led to a need for flexible emergency powers which can be exercised for the prevention of escalating threats. Flexibility of emergency powers is considered as a crucial element of legal resilience. To balance flexible emergency powers, fundamental rights will have to be properly safeguarded. Thus, another crucial element of legal resilience is the legal protection of individual rights, which requires that the authorities exercise their powers in a predictable manner and subject to both judicial and political control. To achieve legal resilience, it is necessary that the arguments for comprehensive national security be systematically coordinated with the protection of fundamental rights. At the same time, the judicial resource needs and the available regulatory solutions linked to legal resilience should be evaluated. The normal requirements of legislative precision and clear definition of statutes should be coordinated with flexible emergency powers. Better legal resilience could be achieved by using a gradual regulation structure with predetermined criteria for the triggering of given emergency powers. In the implementation such legal resilience, it is necessary to consider the dynamics of disruptions. Judicial control should be adjusted to different types of disruption, that is, various slowly or rapidly developing crises and combinations of crises. Legal resilience requires also that the authorities have the proper mindset for exercising their emergency powers in the appropriate, flexible manner.